The Influence of Lifestyle, Religiosity, and Prizes on the Decision of Members to Choose Takop - Qoriani, Hersa Farida (Jurnal Informatika Ekonomi Bisnis, 2021)
This study aims to examine how much influence lifestyle, religiosity, and prizes for the decision of members of KSU Setia Hati , Buduran Sidoarjo in choosing Takop savings. The formulation of the problem in this study is does lifestyle partially influence the decision of cooperative members to choose Takop KSU Setia Hati Buduran, Sidoarjo?. Is religiosity partially significant to the decision of cooperative members to choose Takop KSU Setia Hati Buduran, Sidoarjo?. Does the prize partially influence the cooperative member's decision to choose Takop KSU Setia Hati Buduran, Sidoarjo?. Does lifestyle, religiosity, and prizes simultaneously have a significant effect on the decision of cooperative members to choose Takop KSU Setia Hati Buduran, Sidoarjo?. This study uses a quantitative approach. Data collection was carried out using questionnaires and documentation. The population of this study is members of the Cooperative savings (Takop) in 2020-2021, totaling 105 members. The sample used is saturated sampling using the entire population. The data analysis used is multiple regression analysis. The results of this study indicate that lifestyle has a positive effect on members' decisions, religiosity has a positive effect on members decisions, and rewards have a positive effect on members decisions. Meanwhile, lifestyle, religiosity, and prizes simultaneously affect the members decision to choose Takop in the Setia Hati Sidoarjo Multi-Business Cooperative (KSU).